Vortex Enterprise : Portable Automated Whiteboard Eraser / Muhammad Shufiuddin Sabilan ...[et al.] - Sabilan, Muhammad Shufiuddin; Abd Rahim, Muhammad qayyum; Wan Husain, Wan Azizul Rahman; A. Rahim, Muhammad Razali; Mohamed Noor, Ahmad Khairilanam; Othman, Mohammad Nur Hidayah (2016)
We registered our business on 16 January 2016, while the date of our commercial is on 29 February 2016. Each of us at least has 1 year of working experience. Each of us contributed our money and also loan from bank in order to establish the capital for our business. We have partnership agreement and each of us need to sign it by as to show that we have agreed with the terms and condition. Last but not least, we are expecting that our company, Vortex Enterprise will become a well-known company for providing trusted equipment in the academic Institution that bring benefits to the society and much more to the future.